Perancangan Aplikasi Sistem Pakar Diagnosa Penyakit Ginekologi Menggunakan Metode Forward Chaining Berbasis Web Mobile - Novi Yona Sidratul Munti; Ferri Achmad Effindri (Jurnal Media Infotama, 2017)
The purpose of this research is to build the application of Expert System of gynecology diseases based on web mobile that can facilitate user in diagnose gynecological disease. This research uses Forward Chaining method. The results displayed are user conditions associated with gynecological diseases. Results are also equipped with illness and treatment solutions displayed in the form of website and mobile application using PHP programming with MySQL database. The conclusion in this research is to use Forward Chaining method on Expert System diagnose gynecological disease is very helpful in research and development process Expert System conducted. Expert system diagnosis of gynecological diseases built can make a diagnosis of gynecological diseases based on user-perceived symptoms, then the system will show the diagnosis and provide treatment solutionsKeyword : Expert System, gynecology, Forward Chaining, PHP MySQL